APPROXIMATION OF DIFFERENTIABLE PERIODIC FUNCTIONS BY THEIR BIHARMONIC POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2002)
We determine the exact values and asymptotic decompositions of upper bounds of approximations by biharmonic Poisson integrals on classes of periodic differentiable functions.